Notable Luther and Melanchthon: An Annotated Copy of Luther’s Confitendi ratio - Mann, Jesse D. (Reformation, 2020)
This article addresses an unusual case of annotation in an early Luther imprint. Drew University Library (Madison, NJ, USA) owns a copy of Luther’s Confitendi ratio (Wittenberg, 1520) that, according to the Library catalog, “is heavily annotated in a contemporary hand.” The present article identifies the sources of these annotations and offers some suggestions about the identity of the annotator, as well as some suggestions about the possible reasons or uses for these annotations. It also reflects on the function of annotations in the Kommunikationsprozess. The article suggests that the annotations in this book may have some connection with the Latomus Controversy that engaged Luther and other Reformers in the early 1520s.